Comparison of C4-oxidizing and C1/C4-oxidizing AA9 LPMOs in substrate adsorption, H2O2-driven activity and synergy with cellulase on celluloses of different crystallinity. (1st October 2021) - Chen, Kaixiang; Zhang, Xi; Long, Liangkun; Ding, Shaojun
Abstract: Two C1/C4-oxidizing AA9 lytic polysaccharide monooxygenases (AA9 LPMOs), Ao LPMO9A and Ao LPMO9B, and one C4-oxidizing Ao LPMO9C from Aspergillus oryzae, were characterized and compared with the well-studied C4-oxidizing Nc LPMO9C. Nc LPMO9C and Ao LPMO9C harboring carbohydrate-binding module 1 (CBM1) exhibited much stronger adsorption capacity than Ao LPMO9A and B without CBM1. The binding affinity is crucial for the efficacy of H2 O2 as cosubstrate and oxidative activity of AA9 LPMOs on crystalline cellulose. C4-oxidizing AA9 LPMOs had a striking boosting effect on cellobiohydrolase I (CBHI), while C1/C4-oxidizing AA9 LPMOs boosted CBHII and endoglucanase I (EGI) activity. Our results indicated that two types of AA9 LPMOs with different modularities and regioselectivities varied in cellulose adsorption, H2 O2 -driven activity and synergy with cellulase on celluloses of different crystallinity which could complement each other in lignocellulose degradation. C4-oxidizing AA9 LPMOs with CBM1 were particularly essential in cellulase cocktail due to high H2 O2 -driven activity and a striking boosting effect on CBHI. Highlights: Nc LPMO9C/A o LPMO9C harboring CBM1 exhibited much stronger adsorption on cellulose than AoLPMO9A/B without CBM1. H2 O2 -driven efficacy differed strikingly between Nc LPMO9C/A o LPMO9C and A o LPMO9A/B on cellulose but similar on xyloglucan. A o LPMO9A/B are substitution-tolerant XG-active while Nc LPMO9C/ A o LPMO9C are substitution-intolerant. Nc LPMO9C/A o LPMO9C had a striking boosting effect on CBHI while A o LPMO9A/B had a boosting effect on CBHII and EGI. The crystallinity of cellulose had different effects on the activity of two type AA9 LPMOs and their synergy with GHs.